Prarancangan Pabrik Etil Akrilat dari Asam Akrilt dan Etanol Kapasitas 40.000 Ton/Tahun - Amin, Rizki Khairunnisak Nur; , Kusmiyati, S.T, M.T, Ph.D; , Emi Erawati, S.T, M.Eng (2016)
One of the chemical industry is growing in Indonesia is the production of ethyl acrylate. Ethyl acrylate is a raw material in the manufacturing of polymer solution which is widely used in industrial paints (coatings). In addition, ethyl acrylate is a raw material for polymer emulsion. Of ethyl acrylate emulsion polymers widely used as an adhesive (adhesive), paper, polishing floors, ceramic, textile, leather industry and as copolymers of acrylic fiber. To meet domestic demand still remains to be imported from abroad as well as the availability of opportunities for export that are still open, the plant is designed with a capacity of 40,000 tons / year is planned to operate for 330 days per year. The process of making ethyl acrylate is used in the esterification process flow stirred reactor (RATB) in the liquid-liquid phase, non isothermal adiabatic state at a temperature of 70 ° C da pressure of 1 atm. Acrylic acid raw material requirements of 3840.74 kg / h and ethanol for 2.706,26kg / hour. Support utilities includes supplying process water obtained from river water, the provision of steam amounted to 1339.53 kg / hour, cooling water requirements of 1339.53 kg / hr, water and sanitation needs sebesar2.584,70 consumption kg / hour, demand for electricity can be met from PLN and 1 500 kW generator for backup. Needs compressed air that is equal to 50 m3 / h. The factory is planned to be established industrial area of Cilegon, Banten, with a land area of 20.000m2 and the number of employees 186 people. From the results of the economic analysis prarancangan ethyl acrylate plant obtained a profit after tax of Rp. 62,382,410,641.27, ROI (Return On Investment) after tax 24.67%, POT (Pay Out Time) after tax of 2.88 years, BEP (Break Even Point) 55.67% and SDP (Shut Down Point) 39 , 49%. While the DCF (Discounted Cash Flow) amounted to 32.88%. From the economic analysis done may be concluded that ethyl acrylate plant with a capacity of 40,000 tons / year worth considering for development is realized.